Inclusão digital de agricultores familiares em municípios da região Oeste do Paraná - Bauermann, Henrique Botan (2016)
The aim of this research is to evaluate the training process of the Digital Inclusion Training Project for Solidarity Economy Cooperatives in the Paraná Western region. The research was carried out with family farmers participating in the training proposed by the Digital Networks Program, in the cities of Marechal Cândido Rondon and Palotina, in the Paraná Western region, being, in this way, a digital inclusion diagnosis of family farmers in the aforementioned cities. Data collection was done using electronic questionnaires elaborated using the Google Forms tool. The Digital Inclusion Training Project was developed in the courses form for family farmers, consisting of six basic modules and two advanced ones. The basic modules focused on computing and computer basics applied to farmers' routine activities, while advanced modules were more focused on "extra" activities, such as tendering and marketing. The main results showed that digital inclusion training modified participants' habits and routines, giving them more autonomy and confidence, allowing better access to information, such as weather forecasting, news, training videos, etc., and improving their farms management through spreadsheets.